2018
DOI: 10.1111/jai.13626
|View full text |Cite
|
Sign up to set email alerts
|

Diving activity of migrating silver eel with and withoutAnguillicola crassusinfection

Abstract: Summary Infection with the swim bladder nematode Anguillicola crassus has been hypothesised to threaten the spawning migration success of the endangered European eel (Anguilla anguilla). To examine this assumption, we compared the swimming behaviour of one Anguillicola crassus infested eel in the North Sea and three parasite‐free eels in the Baltic using data recovered from data storage tags attached to migrating silver eels. In both areas, eel activity was characterized by frequent diving behaviour throughout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Laboratory research indicates that infected eels show a more pronounced stress response when exposed to hypoxic conditions (Gollock et al, 2005), that infected silver eels may not be able to reach the spawning area due to the metabolic impacts of the parasite (Palstra et al, 2007), and physiological modelling suggests that the trans‐oceanic migration would be significantly affected (Barry et al, 2014). Field evidence from silver eels migrating along the Swedish Baltic coast confirmed adverse effects on the swimming abilities and survival prospects of A. crassus infected eels (Sjöberg et al, 2009), although other studies have not come to the same conclusion (Simon et al, 2018). It seems certain that a chronic infection with this parasite alone, or associated with other impacts, will affect the ability of eels to migrate and reproduce effectively, but more work is needed on the impacts of A. crassus and how eels are adapting to infestation as it transitions from an acute to a chronic threat.…”
Section: Resultsmentioning
confidence: 92%
“…Laboratory research indicates that infected eels show a more pronounced stress response when exposed to hypoxic conditions (Gollock et al, 2005), that infected silver eels may not be able to reach the spawning area due to the metabolic impacts of the parasite (Palstra et al, 2007), and physiological modelling suggests that the trans‐oceanic migration would be significantly affected (Barry et al, 2014). Field evidence from silver eels migrating along the Swedish Baltic coast confirmed adverse effects on the swimming abilities and survival prospects of A. crassus infected eels (Sjöberg et al, 2009), although other studies have not come to the same conclusion (Simon et al, 2018). It seems certain that a chronic infection with this parasite alone, or associated with other impacts, will affect the ability of eels to migrate and reproduce effectively, but more work is needed on the impacts of A. crassus and how eels are adapting to infestation as it transitions from an acute to a chronic threat.…”
Section: Resultsmentioning
confidence: 92%
“…Five of these included only a limited number (≤ 14) of tracked eels and did not describe any eel exiting the basin 18 22 . Although these studies are limited, they have shown that at least a proportion of the European eels migrate south-westwards towards the English Channel to reach the Atlantic Ocean 18 , 20 , while others seem to migrate north 21 . The two remaining studies, based on a much larger number of individuals, reported a ‘Nordic’ route for eels leaving the Baltic along the Norwegian Trench over the British Isles 12 , 16 ; this route is probably joined by the northward migrating individuals reported in the other studies.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of the parasite may impact on the eel's migration speed in rivers (Newbold et al ., 2015 ) and in the ocean as the energy demand increases (Pelster, 2015 ), due to the reduction of the swim bladder elasticity. The presence of the parasite appears not to affect the speed and migratory behaviour during the first phase of the migration in shallow water (Simon et al ., 2018 ). However, where deep diving is required in the ocean, damage to the integrity of the swim bladder is believed to seriously impact on an infected eel's chances of survival (Lefebvre et al ., 2012 ; Righton et al ., 2016 ).…”
Section: Introductionmentioning
confidence: 99%